Patient reported outcome measures in primary healthcare: A literature review - Silva Ribeiro, Mariana (2023)
The Patient-Reported Outcomes Measures (PROMs) provide the patient’s view of their life quality, functionality, symptoms and satisfaction with healthcare. The present study aims to identify PROMs associated with the reality of primary health care and to understand their possible benefits in clinical practice. An integrative literature review was carried out according to the PICO methodology (Population, Intervention, Comparison, results), in the PubMed, NICE Guidelines Finder, The Cochrane Library databases, using the MeSH terms patients reported results measures and primary health care. This integrative review followed the methodological recommendations of the authors Mendes, Silveira and Galvão. After reading and analyzing the articles included in this review, it was observed that in Portugal there is a lack of research on PROMs in primary health care. Nevertheless, PROMs could be an asset when based on the best and most current evidence available in promoting patient-centered care and improving the quality of care provided in primary health care.